2023
DOI: 10.3389/fnins.2022.1081769
|View full text |Cite
|
Sign up to set email alerts
|

Vigilance or avoidance: How do autistic traits and social anxiety modulate attention to the eyes?

Abstract: IntroductionSocial anxiety disorder (SAD) and autism spectrum disorder (ASD) are highly overlapping in symptoms and have a high rate of comorbidity, posing challenges in diagnosis and intervention for both disorders. Both disorders are linked to abnormal attention to the eyes, yet how they interactively modulate the attentional process to the eyes remains unclear.MethodsIn this study, we explored how autistic traits and social anxiety in college students separately and together affected different temporal stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
(100 reference statements)
0
2
0
Order By: Relevance
“…Moreover, reduced fixation of the eyes in ASD is a common trait. It is observed that early avoidance of the eyes is associated with social anxiety among students with high ASD [ 24 ]. It suggested the reduced fixation of the eyes and poor fear recognition ability influence social anxiety among individuals with ASD since these factors impact the cues and information processing ability necessary for social interaction.…”
Section: Reviewmentioning
confidence: 99%
“…Moreover, reduced fixation of the eyes in ASD is a common trait. It is observed that early avoidance of the eyes is associated with social anxiety among students with high ASD [ 24 ]. It suggested the reduced fixation of the eyes and poor fear recognition ability influence social anxiety among individuals with ASD since these factors impact the cues and information processing ability necessary for social interaction.…”
Section: Reviewmentioning
confidence: 99%
“…The mean AQ score of the sample was 16.2 (M = 16.2; SD = 6.48). In the present study, we considered AQ score levels that deviate from the mean by only one standard deviation as medium-low (-1SD) and medium-high (+ 1SD) levels, while scores that deviate more strongly from the mean (+ 2SD) as high levels (see [41] for a similar procedure). It is to note that the present way to classify the levels of the AQ score matches well the classification proposed by Baron Cohen and colleagues [35].…”
Section: Descriptive Analyses Of the Clean Samplementioning
confidence: 99%